2023
DOI: 10.1007/s00403-023-02538-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of insomnia in the vulnerability to depressive and anxiety symptoms in atopic dermatitis adult patients

Abstract: Atopic dermatitis (AD) is a common inflammatory chronic skin disease typically associated with atopic comorbidities and other non-atopic conditions such as sleep disturbances, and mood/anxiety disorders. A growing literature proposed a crucial role of sleep disturbances in the development of mental health problems in AD. We tested this assumption by mediation model analyses in adult AD patients.A total of 57 patients (mean age ± std. dev., 34.28 ± 13.07 years; 27 males; range 18–67 years) diagnosed with AD par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This study showed a higher incidence of major depression, any depressive disorder, and bipolar disorder in the atopic cohort, with an earlier onset of symptoms [71]. In addition, it was observed that the Beck Depression Inventory and Self-rating Anxiety Scale questionnaires were higher in patients with severe AD [36], in agreement with Salfi et al, who found that more severe forms of AD were associated with more severe symptoms of depression and anxiety [72].…”
Section: Ad and Anxiety/depressive Disorderssupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed a higher incidence of major depression, any depressive disorder, and bipolar disorder in the atopic cohort, with an earlier onset of symptoms [71]. In addition, it was observed that the Beck Depression Inventory and Self-rating Anxiety Scale questionnaires were higher in patients with severe AD [36], in agreement with Salfi et al, who found that more severe forms of AD were associated with more severe symptoms of depression and anxiety [72].…”
Section: Ad and Anxiety/depressive Disorderssupporting
confidence: 89%
“…A recent cross-sectional study observed that more severe AD symptoms were associated with more severe symptoms of insomnia, anxiety, and depression; moreover, the severity of insomnia was correlated with symptoms of anxiety and depression. Thus, insomnia could explain the relationship between AD severity and anxiety/depressive symptoms [72].…”
Section: Ad and Anxiety/depressive Disordersmentioning
confidence: 99%
“…In this regard, sleep disturbance and/or insomnia can even lead to increased anxiety and depression ( 23 ). Indeed, patients with AD, especially those with moderate-to-severe forms of the disease, report high rates of anxiety and depression ( 24 , 25 ). Our results from the systematic review and those reported from HCPs and patients participating in our project confirm those obtained in previous studies, and highlight the relevance of assessing pruritus in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the absence of a causal role of AD in the development of depressive and anxiety disorders has been proposed 44 , supporting the existence of an indirect link between AD and psychological measures driven by other concomitant conditions. In this regard, recent studies suggested that sleep disturbances might predispose AD patients to experience psychological symptoms 45,46 .…”
Section: Discussionmentioning
confidence: 99%